Beyond a mediocre customer experience in the circular economy: The satisfaction of contributing to the ecological transition. (10th December 2022) - Guyader, Hugo; Ponsignon, Frederic; Salignac, Fanny; Bojovic, Neva
Abstract: This article aims to understand and explain the differences in circular (versus traditional) economy consumption habits. It explores the customer experience's role in influencing satisfaction and reuse decisions. Data is collected through a mixed-methods case study. Specifically, the article looks at an innovative ecological sanitation system for urban households aiming at collecting human waste for valorization. Among the participating households, 46 persons provided data: 12 were interviewed about their motives for and experience of using dry sanitation and participating in the waste collection process, 42 answered a user profile survey focusing on demographics and basic individual values, and 36 submitted diary entries (123 in total) providing detailed descriptions and evolutions of their experiences. Based on this rich dataset, the findings highlight that the customer experience is largely inferior to that of using traditional sanitation systems because it is inconsistent, inconvenient and requires significant customer efforts (e.g., voluntary participation, creativity, and bricolage skills). Nonetheless, this mediocre experience is counterbalanced by the customer's personal values and beliefs, as well as the satisfaction of achieving a more responsible and sustainable activity. Highlights: Unique case study of urban ecological sanitation in a circular economy context. Effortful, inconsistent and inconvenient customer experience. Mediocre experience counterbalanced by personal value systems. Satisfaction and loyalty through achieving a responsible and sustainable activity.